Protocol for in vivo recording of neural activity in deep structures of mice brain via gradient lenses by calcium imaging - Stanislav Cherepanov; Patrice Mollard; Agnes O. Martin (STAR Protocols)
Summary: Calcium (Ca2+) imaging is a viable approach for imaging neuronal activity patterns in local brain circuits in living animals. Here, we present a protocol for gradient lens implantation in deep brain structures followed by in vivo Ca2+ imaging. We describe in detail the steps for surgery preparation, followed by lens implantation, setup for awake head-fixed imaging, and the recording process.For complete details on the use and execution of this protocol, please refer to Cherepanov et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.